A Way Forward for Sociological Research on Science and Religion: A Review and a Riff - Ecklund, Elaine Howard (Zygon, 2019)
John Evans's new book Morals Not Knowledge pushes scholars to rethink contemporary debates about religion and science by moving past the rhetoric of societal elites to examine the perspectives of everyday Americans, identifying the moral conflicts at the heart of debates. We review Evans's key contributions while also extending and challenging his arguments, urging consideration of how renewed moral debates might be informed by a broader set of U.S. "publics." Drawing on empirical research, we highlight four sets of voices that are missing from Evans's analysis. Specifically, we highlight the voices of racial and ethnic minorities, religious communities (as opposed to individuals), members of minority religious traditions, and everyday religious scientists. Through doing so we offer avenues for future research on these diverse publics that will help facilitate a broader set of better and more informed debates about moral conflict between religious and scientific communities.